2015
DOI: 10.1002/cctc.201500848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nickel Nanoparticles with N‐Doped Graphene Shells for Catalytic Reduction Reactions

Abstract: The synthesis of novel nanoparticles is of general importance for the development of efficient heterogeneous catalysts. Herein, the preparation of carbon‐supported nickel‐based nanoparticles (NPs), modified by nitrogen‐doped graphene layers, is reported for the first time. The resulting materials were characterized in detail by TEM, X‐ray photoelectron spectroscopy (XPS), XRD, elemental analysis (EA), electron paramagnetic resonance (EPR), temperature‐programmed reduction (TPR), BET, and Raman analysis. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 50 publications
2
50
0
2
Order By: Relevance
“…In Scheme we represent the methodology of synthesis of Fe 3 O 4 nanoparticles via coprecipitation method and then Fe 3 O 4 @N‐doped graphene …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In Scheme we represent the methodology of synthesis of Fe 3 O 4 nanoparticles via coprecipitation method and then Fe 3 O 4 @N‐doped graphene …”
Section: Resultssupporting
confidence: 69%
“… Brief representation of the methodology to synthesize the Fe 3 O 4 nanoparticles via coprecipitation method following a thermal treatment in presence of 1,10 phenanthroline to finally obtain Fe 3 O 4 @N‐doped graphene …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…It has been recently reported that MNPs and metal oxides obtained by pyrolysis of metal complexes can exhibit a unique catalytic activity thanks to the favorable influence of the carbonaceous matrix surrounding the MNPs, which was formed in the process . Similarly, MNPs and metal oxides wrapped with carbon have been obtained by pyrolysis of metal organic frameworks .…”
Section: Introductionmentioning
confidence: 86%
“…Especially, N‐doping of graphene (NGr) can provide remarkable increase in conductivity and electron donor properties owing to the similar atomic size and five valence electrons that are accessible in forming valence bonds with carbon atoms. The introduction of metal nanoparticles on the surface of N‐doped graphene can provide smaller particle size and dispersion of catalyst nanoparticles, strong bonding between the nanoparticles and the support of enhanced electronic structures for the catalyst, and increased electronic conductivity for the support . Recent findings suggest that doped graphene with nitrogen based active sites may exhibit promoted electro‐catalytic activity even in the absence of precious metals ,…”
Section: Introductionmentioning
confidence: 99%